2018
DOI: 10.1017/aog.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and sources of dissolved organic matter in a glacier in the northern Tibetan Plateau: differences between different snow categories

Abstract: Dissolved organic matter (DOM) in mountain glaciers is an important source of carbon for downstream aquatic systems, and its impact is expected to increase due to the increased melting rate of glaciers. We present a comprehensive study of Laohugou glacier no. 12 (LHG) at the northern edge of the Tibetan Plateau to characterize the DOM composition and sources by analyzing surface fresh snow, granular ice samples, and snow pit samples which covered a whole year cycle of 2014/15. Excitation–emission matrix fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
5
6
2
Order By: Relevance
“…The U samples had the highest number of assigned compounds among four groups of sites in both ESI+ and ESI− with averages of 1113 ± 203 and 871 ± 287, respectively (Tables 1 and 2), whereas the number of as-signed species from S samples was lowest (mean: 727 ± 146 and 438 ± 84 for ESI+ and ESI− modes, respectively), reflecting the high molecular complexity of U samples. The numbers of assigned formulas in this study are comparable to the assignments reported for urban aerosol samples (∼ 800-1800) (Lin et al, 2012;Wang et al, 2017a) and WSOC of LHG glacier from the TP region (∼ 700-1900) (Feng et al, 2016(Feng et al, , 2018, but they are lower than those of WSOC from the Antarctic (∼ 1400-2600) and Greenland ice sheets (∼ 1200-4400) (Antony et al, 2014;Bhatia et al, 2010). The mass spectrum plots constructed from individual samples showing integrated composition of U, R, S, and site 120 samples along with the corresponding number contributions from different formula categories are shown in Fig.…”
Section: General Hrms Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…The U samples had the highest number of assigned compounds among four groups of sites in both ESI+ and ESI− with averages of 1113 ± 203 and 871 ± 287, respectively (Tables 1 and 2), whereas the number of as-signed species from S samples was lowest (mean: 727 ± 146 and 438 ± 84 for ESI+ and ESI− modes, respectively), reflecting the high molecular complexity of U samples. The numbers of assigned formulas in this study are comparable to the assignments reported for urban aerosol samples (∼ 800-1800) (Lin et al, 2012;Wang et al, 2017a) and WSOC of LHG glacier from the TP region (∼ 700-1900) (Feng et al, 2016(Feng et al, , 2018, but they are lower than those of WSOC from the Antarctic (∼ 1400-2600) and Greenland ice sheets (∼ 1200-4400) (Antony et al, 2014;Bhatia et al, 2010). The mass spectrum plots constructed from individual samples showing integrated composition of U, R, S, and site 120 samples along with the corresponding number contributions from different formula categories are shown in Fig.…”
Section: General Hrms Characteristicssupporting
confidence: 86%
“…BC is also shown for reference (Bond and Bergstrom, 2006 et al, 2007a, b;Hood et al, 2015), glaciers in the European Alps (∼ 100-300 ng g −1 ) (Legrand et al, 2013;Singer et al, 2012), and the remote TP region (∼ 150-700 ng g −1 ) (Yan et al, 2016). However, our reported WSOC mass concentrations are in the same range as those in the fresh snow samples collected from Laohugou (LHG) glacier, northern TP (2000-2610 ng g −1 ) (Feng et al, 2018). It has been reported that glaciers and ice sheets from polar or alpine regions store a large amount of WSOC and discharge it to their downstream terrestrial ecosystems (Hood et al, 2009(Hood et al, , 2015Singer et al, 2012).…”
Section: Characteristics Of Chemical Speciessupporting
confidence: 79%
“…The U samples had the highest number of assigned compounds among four groups of sites in both ESI+ and ESI-with averages of 1113±203 and 871±287, respectively (Tables 1 and 2), whereas the number of assigned species from S samples were lowest (mean: 727±146 and 438±84 for ESI+ and ESI-modes, respectively), reflecting high molecular complexity of U samples. The numbers of assigned formulas in this study are comparable with the assignments reported for urban aerosol samples (~800-1800) (Lin et al, 2012;Wang et al, 2017a) and WSOC of LHG glacier from the TP region (~700-1900) (Feng et al, 2016;Feng et al, 2018), but they are lower In ESI+ mode, CHO+ and CHON+ were the main components in all samples, accounting for 35% to 61% and 20% to 28% of total formulas, respectively (Table 1).…”
Section: General Hrms Characteristicssupporting
confidence: 87%
“…than those found in the snow and ice from polar regions (~40 -500 ng g -1 ) (Fellman et al, 2015;Hagler et al, 2007a,b;Hood et al, 2015), glaciers on the European Alps (~100 -300 ng g -1 ) (Legrand et al, 2013;Singer et al, 2012), and the remote TP region (~150 -700 ng g -1 ) (Yan et al, 2016). However, our reported WSOC mass concentrations are in the same range as those in the fresh snow samples collected from Laohugou (LHG) glacier, northern TP (2000 -2610 ng g -1 ) (Feng et al, 2018). It follows that in addition to the snow and glaciers from polar or alpine regions, the seasonal snow in Northern Xinjiang is also an important organic carbon source for the covered ecosystems.…”
Section: Characteristics Of Chemical Speciescontrasting
confidence: 38%
“…The U samples showed the lowest CHO+ abundance (mean: 42%±5%) while the sample from site 120 had the highest value (59%). The fractions of CHON+ species in our samples were significantly lower than those of the aged firn/ice samples from the TP (Feng et al, 2016(Feng et al, ,2018(Feng et al, ,2020Spencer et al, 2014) in which WSOC showed high bioavailability; but were comparable with the WSOC samples from fresh snow (Feng et al, 2018(Feng et al, ,2020. These results indicate that WSOC from the snowpack in northern https://doi.org/10.5194/acp-2020-1260 Preprint.…”
Section: General Hrms Characteristicsmentioning
confidence: 56%